Evaluation of a balance and mobility program for older adults at risk of falling: a mixed methods study. Issue 2 (25th May 2020) - Osho, Oluwaseyi A.; Harbidge, Cathy; Hogan, David B.; Manns, Patricia J.; Jones, C. Allyson
Abstract: Rational, aims, and objectives: The FallProof Balance and Mobility Program is a multifactorial fall prevention intervention that targets intrinsic risk factors such as muscle strength, balance, gait, and posture. Using mixed methods, we evaluated the implementation of the program for older adults at high risk of falling in the community. Methods: A pre‐post program evaluation and semi‐structured interviews were used to evaluate FallProof Balance and Mobility Program offered to older adults who were recurrent fallers. Over a 1‐year period, the 12‐week program was offered five times. Feasibility, acceptability, and outcome evaluation along with semi‐structured interviews were done. Over the course of the evaluation, participants were evaluated three times (baseline, 12, and 16 weeks). Results: Of the 19 participants, who enrolled in the program, 16 completed the program and 12 attended at least 80% of the classes. Fourteen participants had mildly impaired cognition (Montreal Cognitive Assessment <26). Large gains (effect size 0.90) were seen with self‐management (Partner‐in‐Health Scale). Participants were very satisfied with the program. Three themes emerged from the semi‐structured interviews: (a) fall‐related benefits, (b) variety of activities and motivating instructors, and (c) deterrents to participation. Conclusion: Findings provided insights into pragmatic issues of implementing a balance and mobility program for older adults at risk of falling. The FallProof program was found to be feasible and acceptable in a small cohort of older adults from the community.